Systemic integration of the sustainability in the evaluation of public policies on the car ownership transition to electric vehicles in Colombia (2021)
¿Ensuring energy security, stopping climate change, and improving urban air quality are three of the main challenges of this century that are being addressed by governments globally. The transport sector contributes significantly to these issues. Sustainable transport involves considering three dimensions¿economic development, environmental preservation, and social development¿ and the transition towards hybrid and plug-in electric vehicles (P/H/EV) is one of its pillars. Sustainable transport is a complex system, with multiple actors and feedbacks between them. Understanding this complexity in an integrated and holistic manner is a challenge that must be addressed. Due to this complexity, a direct assessment of sustainability performance would be imprecise since several issues that may arise due to synergies between the parts of the system would not be identified. This dissertation proposes an integrated approach to understand the synergies between the dimensions of sustainability and the P/H/EV adoption process accounting for the system¿s complexity. The systemic approach facilitates a better understanding of the transport sector and promotes better governmental policies for improving the diffusion of P/H/EV. The model also allows studying the effects of different fiscal policies associated with promoting P/H/EV on Colombia¿s economic, social, and environmental indicators.